Age-dependent response of maize leaf segments to cadmium treatment effect on chlorophyll fluorescence and phytochelatin accumulation - Drazkiewicz, Maria (Journal of plant physiology, 2003)
The relationship between the age of leaf tissue and response of the photosynthetic apparatus and phytochelatin accumulation to Cd treatment was studied. Studies were carried out with seedlings of Zea mays L. cv. Hidosil grown in the presence of 100-200 mumol/L Cd for 14 days under low light conditions. The third leaf was divided into 3 segments of equal length differing in the stage of tissue maturity and used for measurements of chlorophyll content, chlorophyll fluorescence, glutathione and phytochelatin content and Cd accumulation. A close relationship between the age of leaf tissue and response of the photosynthetic apparatus to Cd was shown. Cadmium (200 mumol/L) reduced photochemical processes more in older than younger leaf segments as seen in the Chl fluorescence parameters Fv/F0, and t1/2, while the chlorophyll fluorescence decrease ratio (Rfd) was inhibited more strongly in younger ones. Fv/Fm was slightly affected. Cd-induced enhancement of GSH content was correlated with higher phytochelatin accumulation to a greater extent in younger than in older leaf segments. Phytochelatin level corresponded to changes of photochemical processes in older leaves. The peptide thiol:Cd molar ratio for the phytochelatins varied depending on Cd concentration and age of leaf segments. The protective role of phytochelatins for the photosynthetic apparatus is discussed